Length-weight relationship and relative condition of Scarus ghobban Forsskal, 1775 from Palk Bay - Varghese, Molly; Balachandran, K; Kasinathan, C (Indian Journal of Fisheries, 2016)
Scarus ghobban collected from the Palk Bay, south-east coast of india was subjected to studies on length-weight relationshipas well as condition factor. The length-weight relationship was found to be W= 0.022473519 L2.9040, indicating isometricgrowth of the fish. The relative condition factor (Kn) ranged between 0.8 and 1.5 with a mean value of 1.0.